Production Technology and a Design of Transfer Ports in a Cylinder of a Small-Volume Motorcycle. (2015) - Daňa, Milan; Zetková, Ivana; Schorník, Václav
Abstract: This work deals with the cylinder of the Jawa 50 Pioneer, which has come to the attention of the general public at the present time, primarily because this type of motorcycle is being increasingly used in races. First, it was necessary to map the current state of the cylinder and transfer channels. Subsequently a 3D model of the cylinder was created. Then, the work deals with the structural design of the transfer channels in the aluminium part of the cylinder. Two variant inputs in to the transfer channel were created and the most suitable design was selected to be made. Then a model of the transfer channel was created and stamped in to the body of the cylinder. The conclusion of this work is dedicated to the production of the transfer channels and measuring performance of this modified cylinder. The production of the cylinder was carried out on a CNC milling machine. For measuring torque, the engine brake was used. The main aim of this work is to increase the performance parameters.